2014
DOI: 10.1002/bmc.3398
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous determination of ten flavonoids of crude and wine‐processed Radix Scutellariae aqueous extracts in rat plasma by UPLC‐ESI‐MS/MS and its application to a comparative pharmacokinetic study

Abstract: Radix Scutellariae (RS) is a herbal medicine with various pharmacological activities to treat inflammation, respiratory and gastrointestinal infections, etc. In this study, a rapid, sensitive and selective UPLC-ESI-MS/MS method was developed for simultaneous determination of 10 flavonoids - scutellarin, scutellarein, chrysin, wogonin, baicalein, apigenin, wogonoside, oroxylin A-7-O-glucuronide, oroxylin A and baicalin - from RS aqueous extracts in rat plasma with propyl paraben as internal standard (IS). Chrom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
22
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 38 publications
(25 citation statements)
references
References 14 publications
3
22
0
Order By: Relevance
“…As shown in Figure , all of the five flavonoids exhibited the double‐peak phenomenon after BXD administration, which may be attributed to enterohepatic circulation (Xing, Chen, & Zhong, ), intestinal flora biotransformation (Noh et al, ), site‐specific absorption (Zhang et al, ) or transporter‐involved mechanisms (Kalapos‐Kovács et al, ). This finding was consistent with previous studies (Cai et al, ; Cui et al, ; Tong et al, ). Among these studies, the first absorption peak of baicalin, baicalein, wogonoside and scutellarin that occurred at 4 h was significantly longer than that of crude Radix Scutellariae extract as reported before.…”
Section: Resultssupporting
confidence: 94%
See 1 more Smart Citation
“…As shown in Figure , all of the five flavonoids exhibited the double‐peak phenomenon after BXD administration, which may be attributed to enterohepatic circulation (Xing, Chen, & Zhong, ), intestinal flora biotransformation (Noh et al, ), site‐specific absorption (Zhang et al, ) or transporter‐involved mechanisms (Kalapos‐Kovács et al, ). This finding was consistent with previous studies (Cai et al, ; Cui et al, ; Tong et al, ). Among these studies, the first absorption peak of baicalin, baicalein, wogonoside and scutellarin that occurred at 4 h was significantly longer than that of crude Radix Scutellariae extract as reported before.…”
Section: Resultssupporting
confidence: 94%
“…To study the pharmacokinetics of nine compounds (baicalin, baicalein, wogonoside, wogonin, scutellarin, berberine, coptisine, the ginsenoside Rb1 and ginsenoside Re) in vivo , several analytical methods have been established by HPLC (Li, Zhang, et al, ; Tsai & Tsai, ), UPLC (Chen, Li, et al, ), LC–MS (Xia et al, ; Zhu et al, ), UPLC–MS (Joo et al, ), LC–MS/MS (Feng et al, ; Tong et al, ; Zhang, Ma, Liu, Jiang, & Wang, ; Zhao et al, ) and UPLC–MS/MS (Cui et al, ; Qian et al, ). A pharmacokinetic study of the constituents in one of the composition herbs in BXD has been reported (Wang et al, ), but there are few reports on pharmacokinetic studies of the nine active components after administration of BXD in rats simultaneously.…”
Section: Introductionmentioning
confidence: 99%
“…And the main pharmacokinetic parameters are summarized in Table . After oral administration, the concentration–time curves of BCN, WGS, BCE, WON, OA displayed double peaks phenomenon, and all analytes tested were absorbed rapidly from the rat gastrointestinal tract, which was in accordance with those reported in the literature . The first peak occurred before 1 h and the second peak over the 5–8 h for all analytes after administration.…”
Section: Resultssupporting
confidence: 89%
“…Then, the chemical profile and the content of bioactive compounds in the raw herbal drugs would be changed. Now, it has already been widely accepted as the major mechanism underlying the raw herbal processing .…”
Section: Introductionmentioning
confidence: 99%